PROJECT-BASED LEARNING AND STUDENT LEARNING OUTCOMES IN ELEMENTARY SCHOOLS - Nela Rofisian, DKK (Universitas Islam Negeri Mataram, 2024)
ABSTRACT This research aims to determine the improvement in learning outcomes of grade 4 students at SD 2 Prambanan through the project based learning model. The type of research is classroom action research using the Kemmis & Mc Taggart model, each cycle consists of four stages, namely planning, implementing actions, observing and reflecting. The research subjects were 20 students in grade 4 of SD 2 Prambanan. Data collection techniques use learning observations, learning results tests, and documentation. The data analysis technique is descriptive analysis with percentages. In cycle 1, student learning outcomes reached a completion percentage of 65% with an average score of 74.75. Cycle 2 student learning outcomes reached a completion percentage of 80% with an average score of 80.75. Keyword: Project Based Learning, Learning Outcomes